The impact of in-hospital nutritional status deterioration on treatment outcome of adult gastroenterological patients - Roganović, Branka; Perić, Saša; Janković, Snežana R. (Vojnosanitetski pregled, 2017)
Background/Aim. In the current literature, data on impact of intrahospital changes in patients’ nutritional status on the treatment outcome are limited. The aim of this study was to investigate the relationship between nutritional status deterioration and the treatment outcome among hospitalized gastroenterological patients. Methods. In 650 adult gastroenterological patients nutritional status on admission and at discharge was evaluated using the 6 nutritional status assessment parameters: body mass index, triceps skinfold thickness, mid-upper arm muscle circumference, serum albumin concentration, lymphocyte count and unintentional weight loss. The influence on treatment outcome was tested for the nutritional status on admission, nutritional status at discharge and intrahospital nutritional status deterioration. Results. The incidence of favorable outcome in the non-undernourished and undernourished patients on admission was in the range 93.4–97.3% and 81.2–91.2%, respectively. The incidence of favorable outcome in the non-undernourished and undernourished patients at discharge was in the range 94–97.4% and 80.8–88.1%, respectively. Favorable outcomes were obtained in 95.6–98.9% of the patients without nutritional status deterioration and in 87.1–90.3% of the patients with nutritional status deterioration. Intrahospital nutritional status deterioration significantly influenced the outcome, no matter what assessment parameter had been used (p < 0.001 for all the applied parameters). Furthermore, only the deterioration of nutritional status was found to be an independent predictor of treatment outcome (multivariate analysis Forwald Wald, p £ 0.001; relative risk (RR) = 0.104–0.350; confidence intervals (CI) = 0.037-0.186/0.297–0.657). Conclusion. Deterioration of nutritional status is an independent predictor of adverse outcome.